2004
DOI: 10.1002/jbm.b.30016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of curing history on residual stresses in bone cement during hip arthroplasty

Abstract: During cement curing in total hip arthroplasty, residual stresses are introduced in the cement mantle as a result of curing shrinkage, thermal shrinkage, and geometrical constraints. These high residual stresses are capable of initiating cracks in the mantle of cemented hip replacements. The purpose of this study was to determine the residual stresses in the cemented hip replacements. The finite element method was developed to predict the residual stresses built up in joint arthroplasties. Experimental tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 76 publications
3
18
1
Order By: Relevance
“…Residual strains set up by added thermal contraction will be competing with these improved properties produced by additional monomer conversion [9,35]. Li et al [36] have shown that the peak temperature reached within cement predicts the residual strains that will remain once curing and cooling have occurred. The heated molds would have led to an increased peak temperature reached due to the exothermic reaction in the curing cement and, in turn, to higher residual stresses.…”
Section: Discussionmentioning
confidence: 97%
“…Residual strains set up by added thermal contraction will be competing with these improved properties produced by additional monomer conversion [9,35]. Li et al [36] have shown that the peak temperature reached within cement predicts the residual strains that will remain once curing and cooling have occurred. The heated molds would have led to an increased peak temperature reached due to the exothermic reaction in the curing cement and, in turn, to higher residual stresses.…”
Section: Discussionmentioning
confidence: 97%
“…Cement polymerization normally starts at the warmer cement-bone interface and continues towards the stem-cement interface, creating pores at this interface. Pre-heating the stem modifies the polymerization direction from stem to bone (Bishop et al, 1996;Iesaka et al, 2003;Li et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They found inside-cement hoop stress of 25.2 MPa. In another study, Li et al (2004) developed a kinetic model of bone cement curing using a FE method. For a stem pre-heated at 45 1C compared to a stem stored at room temperature, the compressive radial stresses increased from 4 to 5 MPa at the stem-cement interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies typically apply a generic modulus (reported to vary from 1.5 to 4.1 GPa (Lewis, 1997)) from the literature. An underlying, and often unstated, assumption is that the cement mantle is stress-free prior to loading, but experimental studies have shown that the thermal and volumetric shrinkage during the cure process results in initial stresses in the range of 1-5 MPa (Lennon and Prendergast, 2002;Li et al, 2004;Ramos et al, 2012) and possibly as high as 10 MPa (Roques et al, 2004). These are of a similar order of magnitude to the stresses generated by loading.…”
Section: Simulation Of the Initial Mechanical Environment Of The Bonementioning
confidence: 99%